Depressive Symptoms and Overperception of Airflow Obstruction in Older Adults With Asthma. Issue 7 (30th September 2021) - Feldman, Jonathan M.; Becker, Jacqueline; Arora, Arushi; DeLeon, Jesenya; Torres-Hernandez, Tatiana; Greenfield, Naomi; Wiviott, Allyana; Jariwala, Sunit; Shim, Chang; Federman, Alex D.; Wisnivesky, Juan P.
ABSTRACT: Objective: Older adults are at increased risk for depression and poor asthma outcomes. We examined whether depressive symptoms are associated with overperception of airflow obstruction and a pattern of worse asthma control, but not pulmonary function. Methods: We recruited a cohort of adults with asthma 60 years and older in East Harlem and the Bronx, New York. Baseline measures included the Geriatric Depression Scale, Asthma Control Questionnaire, and Mini Asthma Quality of Life Questionnaire. Spirometry was conducted at baseline to assess pulmonary function. Perception of airflow obstruction was assessed for 6 weeks following baseline by participants entering estimates of peak expiratory flow (PEF) into a programmable peak flow meter followed by PEF blows. Participants were blinded to actual PEF values. The percentage of time that participants were in the overperception zone was calculated as an average. Results: Among the 334 participants (51% Hispanic, 25% Black), depressive symptoms were associated with overperception of airflow obstruction (β = 0.14, p = .029), worse self-reported asthma control (β = 0.17, p = .003), and lower asthma-related quality of life (β = −0.33, p < .001), but not with lung function (β = −0.01, p = .82). Overperception was also associated with worse self-reported asthma control (β = 0.14, p = .021), but not lung function (β = −0.05, p = .41). Conclusions: Depressive symptoms were associated with greater perceived impairment from asthma, but not pulmonary function. Overperception of asthma symptoms may play a key role in the relationship between depression and asthma outcomes in older adults.